(untitled) - Stephen McGloughlin (Upper Saddle River, New Jersey, 2001)
This book is an instruction in multimedia graphic design and interface building, 3D modeling and animation, digital video editing and creation, morphing, digital sound editing, multimedia authoring, web page creation and design, multimedia product creation...
Keywords: multimedia systems